2012
DOI: 10.1111/1440-1630.12000
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand occupational therapists' views on evidence‐based practice: A replicated survey of attitudes, confidence and behaviours

Abstract: New Zealand therapists' evidence-based practice behaviours, skills and attitudes are largely consistent with international comparisons. However, if New Zealand therapists are to enact the ideal of being 'evidence-based' then accessible training in evidence-based practice-related skills is indicated and should include education of what evidence-based practice means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 36 publications
10
49
0
Order By: Relevance
“…Although guidelines provide specific recommendations for rehabilitation, therapists often perceive barriers to the implementation of guidelines and evidence based practice [2,3]. Issues such as therapy selection and prioritisation, provider safety, equipment and space availability and inadequate staffing are some examples of barriers that have been previously identified by rehabilitation therapists [2,3].…”
mentioning
confidence: 99%
“…Although guidelines provide specific recommendations for rehabilitation, therapists often perceive barriers to the implementation of guidelines and evidence based practice [2,3]. Issues such as therapy selection and prioritisation, provider safety, equipment and space availability and inadequate staffing are some examples of barriers that have been previously identified by rehabilitation therapists [2,3].…”
mentioning
confidence: 99%
“…Of the 368 participants (n = 368), a large majority agreed or strongly agreed that supervising a student increased their own knowledge (80%), helped them to be more evidence-based (71%), and was an important part of clinical practice (89%) (Thomas & Law, 2014). Graham, Robertson, and Anderson (2013), who surveyed 1,587 New Zealand OT practitioners, also reported these positive attitudes. Greater than 80% of respondents felt that EBP was useful in everyday practice and overall OT practice, as well as improved client-centered care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reported common barriers to implementing EBP by these occupational therapists mirrored findings in other allied health professions. Barriers were focused on the process of finding appropriate evidence and implementing it, including difficulty defining a clinical question; limited searching and appraisal skills; lack of confidence, training, and familiarity with search strategies; difficulties in using databases, difficulty understanding research terminology, statistics, and critical appraisal skills; a perceived lack of evidence to support the use of specific interventions; and uncertainty if the evidence was applicable to clients and practice (Copley & Allen, 2009;Crabtree et al, 2012;Fruth et al, 2010;Graham et al, 2013;Hankemeier & Van Lunen, 2011;Stronge & Cahill, 2012). In addition, there are environmental barriers, such as lack of time or money to pursue EBP, large caseloads, poor organizational support, limited access to published information, and poor patient compliance (Crabtree et al, 2012;Fruth et al, 2010;Stronge & Cahill, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Physiotherapists appear to rely more heavily on initial education and training when selecting treatment techniques or modalities instead of using scientific evidence to guide practice thus clinical decision making has been guided by personal experience and expert opinion [11]. Research conducted on the attitudes of physiotherapists towards EBP in some medium and high income countries showed that physiotherapists have a positive attitude when it comes to implementation of EBP [7,10,[12][13][14][15]. Factors reported to improve EBP implementation were possession of a postgraduate qualification, being recently graduated or involvement in on-going research [13,14].…”
Section: Introductionmentioning
confidence: 99%